Meanings, Pathways, and Lived Experiences of International Remittances in Rural Household Asset Building : A Qualitative Case Study in Mirab Soro Woreda, Hadiya Zone, Central Ethiopia - Dawit Dafar (International Humanity Advance, Business & Sciences, 2026)
This qualitative study explores how international remittances influence rural household asset building in Mirab Soro Woreda, Hadiya Zone, Central Ethiopia. Focusing on the meanings, utilization pathways, and lived experiences of remittance-receiving households, the research employs in-depth semi-structured interviews, participant observation, and key informant discussions. Findings reveal that households interpret remittances not only as financial resources but also as social and symbolic instruments, influencing decisions regarding consumption, education, and productive investments. Diverse pathways of remittance utilization are shaped by intra-household decision-making, gender dynamics, and socio-cultural norms. Asset-building outcomes predominantly include livestock acquisition, housing improvements, small-scale business ventures, and agricultural inputs. The study contributes to the literature by providing process-oriented, context-sensitive insights, highlighting how remittances are strategically mobilized for economic security and long-term welfare. The findings have implications for policy interventions aimed at enhancing financial literacy, gender-inclusive decision-making, and productive utilization of remittances in rural Ethiopia.